Contemporary Financial Regulations and Generation of Funds: How Generation of Funds Could Contribute to a Quality School-Based Development - Susantha, Prabath; Lalitha Kumari, H. M. (Researchparks Publishing, 2023)
The Programme for School Improvement (PSI), which has been in operation island wide since 2010, is now amended as “Empowering the Programme for School Improvement (EPSI)”. In line with this amendment, the school development executive committee-the administrative authority of a government schools in Sri Lanka, has also been empowered than before. As a result, some schools do find it easy to raise funds for educational development activities while some others find it hard do so. This imbalance is the research question of this study. Accordingly, the prime objective of this study was to investigate how generation of funds could contribute to a quality school-based development. This study was based on the government schools in the Rathnapura Education Zone in Sri Lanka. As the study used both a qualitative and a quantitative approach simultaneously, it fell into the paradigm of mixed methodology. This study was conducted in discovering the strategies used by the school administration in generating sufficient funds for educational development activities. It also studied the nature of fund generation of the schools in the Zone. It investigated the motivating factors that lead the committee generating enough funds. It also investigated the issues and challenges that prevented an enough amount of fund being sourced. Data collected through the reports, interviews and questionnaires were descriptively analyzed on SPSS and NVivo software interfaces. They were also used in variance analysis, factor analysis and even in thematic analysis too. It revealed from this study that private funds were the major source of funds for financing educational development activities of the schools in the Zone. However, as the type of school, the grades taught, and the number of students studying changed so did the nature and extent of school financing. Motivation of well-wishers and the members of the executive committee were decisive in generating an adequate amount of funds. Time taken to approve school plans prevented funds being sourced adequately. Establishment of school financial management units, the identification of alternative investment opportunities for the school's physical resources, the introduction of school financial reporting standards equipped with a financial reporting system would lead to a higher amount of funds generated and thereby enhance the qualitative development of the Sri Lankan school system- the study unveiled.